Opinions of Senior Students of a Vocational Health High School about Profession of Nursing - Gül Dikeç; Sinem Karakurt; Aylin Bayram; Büşra Zeybek; Dilek Dağlı (Sağlık ve Hemşirelik Yönetimi Dergisi, 2017)
INTRODUCTION: This study was conducted in order to determine the opinions of senior students of the nursing department of a vocational health high school in İzmir about the profession of nursing. METHODS: Research data were collected from three vocational and technical anatolian high schools in İzmir from 20 March to 10 April 2016. In total, 246 senior students took part in the research. In the collection of the data, the questionnaire form which consists of 32 questions concerning the socio-demographic features of the students and their opinions about the profession of nursing and were developed by the researchers. RESULTS: It was determined that 66.4% of the students participating in the research chose the vocational health high school intentionally. When the reasons of the students to choose the school were examined, it was seen that 45.3% of them chose for employment opportunities, 9.3 % of them chose since it was in the health sector, 7.3% of them chose because of the score suitability, 7.7% of them chose since they are fond of helping people, 6.5% of them chose due to the suggestions of the people around and 6.1% of them chose by considering it to be open to development. It was determined that 38.9% of the students did not want to pursue the profession of nursing, 34.8% of them were hesitant and 42.9% of them were reluctant to continue with the undergraduate education. When whether or not the students love the profession was examined, it was determined that 49% of them love the profession, 17% of them do not love the profession and 34% of them are hesitant. DISCUSSION AND CONCLUSION: As a result, it was determined that the students who love nursing have more positive thoughts about the nursing, they found nursing more professional, and they have future plans for education and working.